DNAs of two molecularly cloned endogenous ecotropic proviruses are poorly infectious in DNA transfection assays. - Copeland, N G (1984)
Endogenous ecotropic murine leukemia virus expression varies with inbred mouse strain and age. The mechanism(s) regulating virus expression is unknown, but expression is thought to be controlled at the transcriptional level by linkage to cis-acting cellular DNA sequences or DNA methylation or both. To begin to differentiate between these different control mechanisms, we molecularly cloned two endogenous ecotropic proviruses, Emv-3 and Emv-13, complete with flanking cellular DNA sequences. Both proviruses are poorly expressed in vivo and in vitro, although they appear to be structurally nondefective by restriction enzyme analysis. Cloned DNAs of both proviruses were poorly infectious in DNA transfection experiments, suggesting that methylation may not regulate the expression of these genes in vivo. Removal of their flanking cellular sequences did not increase their infectivity. However, these DNAs were highly infectious when mixed together, indicating that both proviruses carry mutations, that inhibit their expression and belong to different complementation groups. Marker rescue experiments suggested that Emv-3 is defective in the gag region and Emv-13 is defective in p15E-U3. The infectivity of Emv-3, but not of Emv-13, DNA was increased by the addition of AKR xenotropic murine leukemia virus DNA, consistent with known regions of homology between ecotropic and xenotropic proviruses. Recombination between defective endogenous viruses also appears to occur in vivo, suggesting that this may be a common mechanism controlling endogenous murine leukemia virus expression.